Nonlinear absorption and low-threshold two-photon pumped amplified stimulated emission from FAPbBr3 nanocrystals - Wang, Yajuan (2024)
Formamidinium lead bromide （FAPbBr3） nanocrystals （NCs） have been considered to be a good optoelectronic material due to their pure green emission， excellent stability and superior carrier transport characteristics. However， two-photon pumped amplified spontaneous emission （ASE） and the corresponding nonlinear optical properties of FAPbBr3 NCs are scarcely revealed. Herein， we synthesized colloidal FAPbBr3 NCs with different sizes by changing the molar ratio of FABr/PbBr2 in the precursor solution， using ligand assisted precipitation （LARP） technology at room temperature. Photoluminescence （PL） and time resolved photoluminescence （TRPL） spectroscopy were measured to characterize their ASE properties. And their nonlinear optical properties were studied through the Z-scan technique and the two-photon excited fluorescence method. The stimulated emission properties including one- and two-photon pumped ASE have been realized from FAPbBr3 NCs. With large two-photon absorption coefficient （0.27 cm/GW） and high non-linear absorption cross-section （7.52×105 GM）， ASE with threshold as low as 9.8 μJ/cm2 and 487 μJ/cm2 have been obtained from colloidal FAPbBr3 NCs using one- and two-photon excitations. These results indicate that as a new possible green-emitting frequency-upconversion material with low thresholds， FAPbBr3 NCs hold great potential in the development of high-performance two-photon pump lasers.